Social Aspects of the Demographic Situation in Uzbekistan - Kaxramon Kayumov (İmgelem)
This article investigates the sociocultural dimensions of the demographic landscape in Uzbekistan, with a particular emphasis on population expansion, urbanization processes, and transformations in familial structures. The demographic populace of Uzbekistan has exhibited consistent growth, surpassing 36 million individuals in the year 2023, characterized by an annual increase rate of 1.5%. Current urbanization patterns indicate that half of the populace now inhabits urban locales, thereby engendering challenges in educational access, healthcare provision, and employment opportunities. The research employs data derived from national censuses alongside academic investigations to scrutinize these dynamics and offers policy recommendations aimed at alleviating their societal repercussions. Also, in this article, an attempt was made to predict the demograqfic state of birth, marriage, employment, urbanization and its prospective state in Uzbekistan.